Transmission problem between two Herschel-Bulkley fluids in thin layer - SAF, Salim; MESSELMI, Farid; MOSBAH, Kaddour (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
This paper is devoted to the study of steady-state transmission problem between two Herschel-Bulkley fluids in thin layer. Mathematics Subject Classification (2010): 76A05, 49J40, 76B15.